Pemberdayaan Perempuan Untuk Berkarir dan Berbisnis Melalui Platform Digital Instagram @wewaw.id - Hidayati Purnama; Joko Santoso; Agung Kurniawan (PADARINGAN (Jurnal Pendidikan Sosiologi Antropologi), 2025)
Instagram is an effective digital platform for women's empowerment. Instagram has features to turn personal accounts into professionals, one of which is the community. The presence of digital communities certainly supports women's empowerment, including WEWAW (Women Empower Women at Work) with a commitment to provide references, education, and assistance for Indonesian women in their careers and businesses. This research aims to analyse how the content and programs on Instagram @wewaw.id represent efforts to empower women to have a career and do business. This research uses qualitative methods with content analysis techniques, collects data through Instagram accounts and literature studies from documents and books, and uses data triangulation by utilising several different sources of information. The results showed that the wewaw community successfully empowered women through seven stages of empowerment: awareness, freedom, capacity building, empowerment, achievement of results, evaluation, and a follow-up stage. The community uses symbols such as feminine colours, cartoon illustrations of women, and keywords such as "career" and "business" to represent women's social identity. In conclusion, wewaw is a clear example of digital women's empowerment through Instagram that has succeeded in shaping a new social identity for women through the symbols, colours and keywords used consistently in the campaign, and has become a safe and strategic space to build new meanings of independent women.